Trees structure and composition on logged over forest at Kopiyo Meratus, Hulu Sungai Tengah District, South Kalimantan - Asep Sadili (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2016)
Natural forest area in Kalimantan has changed drastically. The aim of this study was to reveal the diversity of tree in Kopiyo Forest of Meratus after termination of Forest Concession was over. Study was carried out at two different observation sites with square method (slope and drier especially). The obtained data was varied, which diversity in the sapling group in two site was 32 species, 28 genera, 25 families, and density of 285 individu-als/ha, with basal area ± 9.50 m2/ha. Whereas, diversity in the tree group in two site was 34 species, 28 genera, 23 families, and density of 485 individual/ha, basal area ± 32.85 m2/ha. Gordonia cf. borneensis was the most dominant species of sapling group in site I and II, and Macaranga hypoglauca was the most dominant species of the tree group in site I and II. Euphorbiaceae, Dipterocarpaceae, Sapindaceae, Myrtaceae, and Rubia-ceae were mostly found in observation sites. Shorea parvifolia, S. pinanga, and S. Smithiana were species with endanger status.